NF-κB as the main node of resistance to receptor tyrosine kinase inhibitors in triple-negative breast cancer - Behrad Darvishi; Leila Farahmand; Zahra Eslami-S; Keivan Majidzadeh-A (Tumor Biology)
Graphical abstract Although accounting for merely a minute portion of diagnosed breast cancers, disproportionate number of deaths and associated low survival rate of patients have made triple-negative breast cancer to be considered as the most lethal breast cancer subtype. More importantly, intrinsic or developed resistance to chemotherapeutic regimens and disappointing outcomes of trials associated with many newly developed agents are other obstacles in establishment of a durable response in these patients. Interestingly, these happen despite the outstanding preclinical outcomes observed by these agents, most importantly among them, targeted receptor tyrosine kinase inhibitors. Pursuing these disappointing outcomes, especially in the case of targeted receptor tyrosine kinase inhibitors, many researches have focused on identification of the hidden factors involved. Highly inflammatory, rich in reactive oxygen species, and hypoxic microenvironment of triple-negative breast cancer tumors and the involving mediators were the first suggestions for observed resistance and poor clinical outcomes of targeted receptor tyrosine kinase inhibitors. Interestingly, for all aberrantly expressed mediators observed in microenvironment, downstream pathways converge in a common node, nothing but the nuclear factor-κB, the insidious factor proposed to be the cause of many events opposing achievement of a desired outcome. In first section of current review, we describe the signaling pathways underlying activation of receptor tyrosine kinases and their convergence at the nuclear factor-κB node, and in next section, we demonstrate how unique hypoxic, inflammatory, rich in free-radical microenvironment of triple-negative breast cancer exacerbate pathways in which otherwise could become mostly suppressed by receptor tyrosine kinase inhibitors.